Pelatihan penyusunan modul ajar akomodatif bagi guru di sekolah dasar inklusif - Utomo Utomo; Imam Yuwono; Eviani Damastuti; Siti Jaleha; Rona Wulandari (Nur Science Institute, 2026)
This community service activity aimed to improve teachers’ understanding and competence in compiling accommodative teaching modules (modul ajar akomodatif) at one of the inclusive schools in Banjarbaru city. A preliminary survey identified several problems: limited teacher understanding of inclusive education paradigms, insufficient knowledge in developing accommodative curricula, and an absence of structured training to create teaching modules tailored to students with special needs. The activity was conducted on June 6, 2024, using a training method that included lectures and a workshop, involving 25 teachers from schools within the same school cluster. Pre- and post-test assessments were administered to measure knowledge improvement. Results showed a significant increase in average scores from 60.4 (pre-test) to 82.4 (post-test). Post-activity evaluation indicated that participants were highly satisfied with the training content, delivery, and relevance to their professional needs. Teachers were also able to independently produce accommodative teaching modules aligned with the specific needs of students with special needs in their respective schools. This training demonstrates that structured professional development programs are effective in enhancing teachers’ pedagogical competence in inclusive education settings.